Control previo y gestión administrativa en la unidad de gestión educativa local de Ucayali Contamana, 2024 - Flores Palomino, Nelson Carlos (2025)
The objective of the research study was to determine the relationship between prior control and administrative management in the Local Educational Management Unit of Ucayali Contamana, 2024. It was a basic descriptive correlational research with a non-experimental design. The study population was composed of 73 workers from the aforementioned entity, who were the main informants for the development of the study. The results allowed us to conclude that prior control in the UGEL Contamana is rated as regular, with an index of 29%. This is because some workers show indecision when accessing the amounts provided for in the regulations, and prior authorization is granted for the execution of additional budgets for the works. Likewise, administrative management was also rated as regular, with an index of 29%. These findings reflect a situation in which, in certain cases, the UGEL has a clear and well defined mission, which contributes to the establishment of its strategic direction. Finally, it was found that there is a strong positive relationship between prior control and administrative management through the Spearman Rho correlation test, which shows a coefficient of 0.803 and a significance of 0.000.